VD_FINDINFO HC / 2010 / 648 vom 19. Juli 2010 - VD Tribunal cantonal (2010)
IN DUBIO PRO REO, APPRÉCIATION DES PREUVES, FAUX MATÉRIEL DANS LES TITRES | 251 ch. 1 CP, 411 let. g CPP, 411 let. i CPP, 415 CPP, 431 al. 2 CPP